STRATEGI PENGEMBANGAN POTENSI OBJEK WISATA DI PULAU BURUNG KABUPATEN TANAH BUMBU - Fitria Naimatin Khasanah; Abdi Fithria; Khairun Nisa (Jurnal Sylva Scienteae, 2022)
The development of tourism potentials is necessary to attract tourists to visit tourism objects. There is a wide range of potential that can develop to manage tourist attractions are flora, fauna, culture, natural attractions, facilities, and infrastructure. The purpose of this research is to identify and inventory the potential of tourism objects, analyze public perception on the development of potential tourism objects, and analyze the development strategy of potential tourism objects on Burung island. This method of research is by interviews and observation of tourist attractions. Determination of respondents using Accidental Sampling and Purpose Sampling methods. Data on interviews and observation results are analyzing in descriptive analysis and SWOT analysis (Strength, Weakness, Opportunities,Threats). Burung Island has a variety of potential tourism objects that need to be developed again, the diversity of flora found 59 species and the number of fauna 68 species, and there are some unique cultures. The facilities and infrastructures in Burung Island are already supporting this tourist attraction. The result of the perception of respondents showed positive results towards the development of this tourist attraction. Based on SWOT analysis, the development of tourism objects on Burung Island is in Quadrant I, so it is necessary to develop Strength-Opportunities (S-O) strategy that is the power used to achieve the most opportunities so that this tourism place can develop betterPengembangan pengelolaan potensi wisata sangat diperlukan untuk menarik wisatawan datang berkunjung kesuatu objek wisata. Terdapat berbagai macam potensi yang dapat dikembangkan untuk mengelola tempat wisata yaitu flora & fauna, kebudayaan, atraksi alam serta sarana & prasarana. Tujuan dari penelitian ini ialah untuk mengidentifikasi dan inventarisasi potensi objek wisata, menganalisis persepsi masyarakat terhadap pengembangan potensi objek wisata serta menganalisis strategi pengembangan potensi objek wisata di Pulau Burung. Metode penelitian ini ialah dengan wawancara dan observasi tempat wisata. Penentuan responden menggunakan metode Accidental Sampling dan Purposive Sampling. Data hasil wawancara dan observasi dianalisis secara analisis deskriptif dan analisis SWOT (Strength, Weakness, Opportunities, Threats). Pulau Burung memiliki berbagai potensi objek wisata yang perlu dikembangkan lagi, keberagaman flora ditemukan 59 spesies dan jumlah fauna 68 spesies serta terdapat beberapa kebudayaan yang unik. Sarana dan prasarana di Pulau Burung sudah cukup menunjang tempat wisata ini. Hasil persepsi responden menunjukkan hasil yang positif terhadap pengembangan tempat wisata ini. Berdasarkan analisis SWOT, pengembangan objek wisata Pulau Burung berada di Kuadran I, sehingga perlu pengembangan strategi Strength-Opportunities (S-O) yaitu kekuatan yang dimanfaatkan untuk meraih peluang sebanyak-banyaknya sehingga tempat wisata ini dapat berkembang lebih baik.